Strategies for Maintaining Household Harmony in the Context of Living With the In-Laws in Mama Ira's Family - Zakiyah Nur Azizah; Hasbi Fajar Achsan; Siti Yusronila (Lembaga Yasin AlSys, 2026)
Multigenerational living arrangements, particularly co-residence with in-laws, are prevalent in rural Indonesia, driven by filial piety, economic considerations, and the need for elder care amid ongoing urbanization; however, empirically grounded analyses of culturally attuned mechanisms that sustain household harmony in such settings remain limited. This study examines strategies for maintaining household harmony in a multigenerational co-residence through the case of Mama Ira’s family in Dusun Jati Gabahan, with a specific focus on how religious values such as birrul walidain are integrated into everyday family dynamics. Using a descriptive qualitative approach, data were collected through in-depth interviews, observations, and documentation from three purposively selected informants (Mama Ira, her husband, and her in-laws), and analyzed thematically with source triangulation to ensure validity. The findings indicate that voluntary co-residence is primarily motivated by moral responsibility and emotional support, and is sustained by flexible division of roles—where in-laws contribute through trading and childcare while the nuclear family manages domestic tasks—alongside clear financial boundaries, open communication, and spousal consultation in resolving conflicts. Religious practices, including mutual reminders for prayer and shared Quranic study, reinforce harmony through the internalization of sabr (patience) and tasamuh (tolerance), while parental authority (aulawiyah) serves to balance differences in childrearing approaches. These dynamics collectively exemplify keluarga sakinah, fostering spiritual cohesion and minimizing resentment, and offer contextually grounded insights for family scholars and policymakers seeking to promote intergenerational solidarity through equitable role arrangements, communicative boundaries, and faith-based resilience in collectivist societies.